2015
DOI: 10.2174/1574362410666150205165504
|View full text |Cite
|
Sign up to set email alerts
|

Strategies of Functional Foods Promote Sleep in Human Being

Abstract: Sleep is a vital segment of life, however, the mechanisms of diet promoting sleep are unclear and are the focus of research. Insomnia is a general sleep disorder and functional foods are known to play a key role in the prevention of insomnia. A number of studies have demonstrated that major insomnia risk factors in human being are less functional foods in dietary. There are higher functional components in functional foods promoting sleep, including tryptophan, GABA, calcium, potassium, melatonin, pyridoxine, L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 116 publications
0
27
0
1
Order By: Relevance
“…Vitamin D may be involved in the prevention of neurodegenerative disorders; alpha-tocopherol, one of the compounds of the vitamin E group, is involved in nervous membranes protection from oxidative damage [26]. Among minerals, manganese, zinc, and copper participate in enzymatic mechanisms protecting against oxidative stress; iron plays a role for oxygenation, energy production, and neurotransmitters and myelin synthesis in the cerebral parenchyma; and calcium, potassium, and magnesium modulate sleep through the proper functioning of ion channels [27].…”
Section: Role Of Nutritional Components On the Brain: Micro-and Macromentioning
confidence: 99%
“…Vitamin D may be involved in the prevention of neurodegenerative disorders; alpha-tocopherol, one of the compounds of the vitamin E group, is involved in nervous membranes protection from oxidative damage [26]. Among minerals, manganese, zinc, and copper participate in enzymatic mechanisms protecting against oxidative stress; iron plays a role for oxygenation, energy production, and neurotransmitters and myelin synthesis in the cerebral parenchyma; and calcium, potassium, and magnesium modulate sleep through the proper functioning of ion channels [27].…”
Section: Role Of Nutritional Components On the Brain: Micro-and Macromentioning
confidence: 99%
“…11) Over the past few decades, many studies have reported that extracts or active components from natural plants are able to bind to the GABA A -BZD receptor to play a sleep-promoting effect. 12,15) Lettuce and skullcap have been known to be two of the herbs that possess sedative effects, although systematic study on their sleep-promoting effects and relevant mechanism has been insufficient. Traditionally, lettuce has been suggested to have sedative-hypnotic properties.…”
Section: Discussionmentioning
confidence: 99%
“…11) Several natural herbs have been known to have a positive role in sedation or sleep. 12) Valerian (Valeriana officinalis), hops (Humulus lupulus), St. John's wort (Hypericum perforatum), chamomile (Matricaria chamomilla), lingzhi (Ganoderma lucidum), barley grass, and maca are natural herbs commonly used as sedatives and anti-anxiety agents in Europe, the U.S.A., and Asia. 13) These herbs contain complex mixtures of flavonoids, terpenes, and related substances, and are known to cross the blood-brain barrier (BBB) to influence brain function.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Barley grass powder with higher GABA, Ca, K, and tryptophan contents is a very effective functional food in promoting sleep [ 70 ]. Sleep symptoms are associated with intake of specific dietary nutrients including Ca (OR = 0.83) and K (OR = 0.70) [ 71 ].…”
Section: Preventive Chronic Disease Of Barley Grassmentioning
confidence: 99%